Direct-to-consumer testing: benefits and concerns of commercially accessed laboratory tests - Orth, Matthias; Sandberg, Sverre; Shih, Patti (Clinical chemistry, 2025)
Promoting self-empowerment of patients and of healthy persons in contemporary health cultures shifts the imperative for initiating laboratory tests from the healthcare professionals (HCP) to the patients themselves.Laboratory testing requested directly by patients without interaction by HCP is called DTCT (direct-to-consumer testing). DTCT is not conducted within traditional healthcare systems, and the regulations that protect the patients in healthcare are not necessarily present in DTCT. Aggressive marketing of DTCT may mislead the consumer, resulting in psychological, physical, and financial harm. The benefit of laboratory testing is dependent on being used on selected persons, with samples collected and stored appropriately, measured with an adequate technique and the test results interpreted properly. DTCT can empower patients, but consumer knowledge varies and currently, there is a lack of reliable resources for consumers to consult. In the absence of healthcare protection rules for DTCT, the concept of informing consumers concurrently with marketing DTCT by the vendors is not in place.DTCT might be advantageous over traditional testing settings in a few selected situations but has a substantial risk of medicalization of healthy persons and damaging the trust in the reliability of healthcare laboratory testing.
Online veröffentlicht: 18. Februar 2025
Gesehen am 17.07.2025